Nexus of Money Function and Its Effect on Inflation Rate in Thailand and Indonesia - Badrudin, Rudy; ., . (International Journal of Engineering and Technology, 2018)
This study aims to investigate the development function of money. At the beginning, function of money is a barter between two commodities, C and C'. Then this becomes C-M-C' when the money is once introduced. The M-C-M' occurs when a businessman utilizes the money (M) to produce commodity (C) and resells it to generate more money (M'). Finally, the trading process of M - M' shows the capital or financial market, like the money or security market. The development of the function of money is shown by the changes of the money supply that measured with the inflation rate. This study contributes to advise the central bank in Thailand and Indonesia in managing the role of the central bank's credibility in achieving the inflation target and the proposed rules on monetary policy. Based on the data of 1990-2015 and using ANOVA and the regression analysis (Î± = 5%) the results show that 1) there is a significantly difference between the currency outside, demand deposits, and quasi-money; 2) the currency outside and the demand deposits in-significantly affects on the inflation rate; 3) the quasi money in-significantly affects and significantly affects on the inflation rate in Thailand and Indonesia.Â Â